"ALPHABET SOUP": Examining Acronym and Abbreviation Style in Headlines. (8th August 2020) - Appelman, Alyssa
ABSTRACT: Through a content analysis and survey, this project explores the prevalence and clarity of acronyms in news headlines. Acronyms popular in a local newspaper were largely unknown to a sample of target readers. When asked about their reactions to unfamiliar published acronyms, about half said they would try to figure it out, and about one-third expressed negative emotions (e.g., frustration, annoyance). Additionally, most said unfamiliar acronyms affect their desire to continue reading, at least some of the time. These findings suggest that an increased focus on comprehension over brevity could help journalists better engage their readers.